Risk Factors for Prolonged Postoperative Ileus in Adult Patients Undergoing Elective Colorectal Surgery: An Observational Cohort Study - Ceretti, Andrea P.; Maroni, Nirvana; Longhi, Marco; Giovenzana, Marco; Santambrogio, Roberto; Barabino, Matteo; Luigiano, Carmelo; Radaelli, Giovanni; Opocher, Enrico (Reviews on Recent Clinical Trials, 2018)
Purpose: Prolonged Postoperative Ileus (PPOI) after abdominal surgery may affect unfavourably the patient recovery. The aim of this study was to estimate the incidence of PPOI in patients elective for colorectal resection and investigate perioperative variables associated with PPOI. Methods: A consecutive series of 428 patients undergoing colorectal resection (median age 72, range 24-92, years; men/women ratio 1.14) were analyzed. Data were extracted retrospectively throughout a five-year period from an electronic prospectively maintained database. PPOI was defined as the need for postoperative insertion of a nasogastric tube in a patient experiencing nausea and two episodes of vomiting and further showing absence of adequate bowel function (absence of flatus/stool) with lack of bowel sounds and abdominal distension. Results: Incidence of PPOI was 7% [95% confidence interval (95%CI), 4.8-9.9%]. Mean hospital stay was 8 days longer in patients with PPOI. Male gender, cancer, cardiac and respiratory co-morbidity, rectal resection, open/converted access, duration of operation, stoma formation and body mass index were associated with PPOI at univariate analysis (0.001< P< 0.048). PPOI was independently associated with male gender [adjusted odds ratio (OR), 4.2; 95%CI, 1.5-11.5], stoma formation (OR, 2.8; 95%CI, 1.2-6.8) and obesity (OR of obese vs. normal weight patients, 3.8, 95%CI, 1.2-12.0). Conclusion: After colorectal resection, PPOI leads to a prolonged hospital stay and slower patient's recovery. An international standardized definition of PPOI is strongly needed to make comparable results from researches and to reliably identify patients with increased risk, also to improve the therapeutic preventive policies in these patients.
Keywords: prolonged postoperative ileus